Characteristics of invasive Acinetobacter infection: A multicenter investigation with molecular identification of causative organisms. Issue 5 (May 2020) - Kiyasu, Yoshihiko; Hitomi, Shigemi; Funayama, Yasunori; Saito, Kazuhito; Ishikawa, Hiroichi
Abstract: We examined microbiological and clinical characteristics of invasive Acinetobacter infection occurring in four hospitals located in the Minami-Ibaraki Area. Glucose-non-fermentative Gram-negative bacilli isolated from the blood and the cerebrospinal fluid in independent cases between 2001 and 2014 were consecutively collected and those possibly to be Acinetobacter species were re-identified using molecular methods. Of 158 strains identified as Acinetobacter species, 155 were classified into 16 officially designated species, including 42 Acinetobacter pittii and 40 Acinetobacter baumannii . Imipenem non-susceptibility was detected only in 4 strains, none of which demonstrated multidrug resistance. Retrospective analyses of 154 cases for which medical records were fully available showed that the most common cause of infection was primary bloodstream infection (134 cases), of which 128 were related to intravascular catheter use. The mortality on day 28 after the onset was independently associated with cerebrovascular disease, moderate to severe renal disease, the Pitt bacteremia score, and infection other than primary bloodstream infection but not with appropriate empiric antimicrobial therapy. Isolation of A. baumannii was significantly associated with septic shock but not with the 28-day mortality. These findings, obtained in a region where drug-resistant Acinetobacter strains were much less prevailing, indicated that non- baumannii Acinetobacter species were common pathogens, that the most predominant cause of invasive Acinetobacter infection was intravascular catheter-related infection, that virulence of A. baumannii might be higher than those of other species but its association with mortality was unclear, and that administration of broad-spectrum antibiotics targeting Acinetobacter species might be deferrable in a certain situation.